Tree growth divergence from winter temperature in the Gongga Mountains, southeastern Tibetan Plateau. Issue 1 (2nd January 2020) - Li, Jingxian; Li, Jinbao; Li, Teng; Au, Tsun Fung
ABSTRACT: The reduced sensitivity of tree growth to temperature in recent decades, commonly known as the tree-ring "divergence problem", has been observed in many places of the world, which challenges the validity of dendroclimatic reconstructions. The manifestation and specific causes of the divergence vary in different environments, yet few studies have attempted to investigate its occurrence on the Tibetan Plateau. Here we report two temperature-sensitive ring-width chronologies of Abies georgei Orr and Sabina tibetica in the Gongga Mountains, southeastern Tibetan Plateau. Significant positive correlations were detected between tree-rings and minimum temperatures, in particular in the prior winter (previous December to current March). Pronounced warming of local temperature was identified in the late twentieth century, with the minimum temperature increasing more rapidly than the mean and maximum temperatures. Concurrently, the tree-ring divergence problem was observed after 2003 at our sampling sites. A loss of sensitivity to winter temperature is coincident with a strengthening of positive (negative) response to the current (previous) growing season temperatures, indicating the complexity and possible multi-causality of the divergence at our sites.